Process building plan approval for 3 storey bungalow with swimming pool / Fatini Izzati Mustafa - Mustafa, Fatini Izzati (2016)
Approval plans is plans approved by the local authority in accordance with Uniform Building By Law (1985) and Act 133, Street Drainage and Building 1974. It is involved which many parties. There are a qualified persons who are architect, engineer and registered building draughtsman, internal and external technical agency. Plan must be submit in 3 copies and 1 set of linen. Building plan must contains key plans, location plans, site plans, floor plan, front elevation, rear elevation, left elevation, right elevation, section plan and roof plan.